2016
DOI: 10.1016/j.neuron.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Memory-Relevant Mushroom Body Output Synapses Are Cholinergic

Abstract: SummaryMemories are stored in the fan-out fan-in neural architectures of the mammalian cerebellum and hippocampus and the insect mushroom bodies. However, whereas key plasticity occurs at glutamatergic synapses in mammals, the neurochemistry of the memory-storing mushroom body Kenyon cell output synapses is unknown. Here we demonstrate a role for acetylcholine (ACh) in Drosophila. Kenyon cells express the ACh-processing proteins ChAT and VAChT, and reducing their expression impairs learned olfactory-driven beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
209
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(234 citation statements)
references
References 91 publications
(143 reference statements)
23
209
2
Order By: Relevance
“…We found that KCs are cholinergic (as in (Barnstedt et al, 2016; Perrat et al, 2013)), the DAL neuron is GABAergic (previously shown by (Chen et al, 2012)), both the MBON-γ5β′2a and MBON-β2β′2a neurons are glutamatergic (consistent with the findings of (Aso et al, 2014b)), and the MBONα3 and V2 neurons are cholinergic (previously shown by (Placais et al, 2013) and (Sejourne et al, 2011)). We detected evidence of potential octopamine synthesis in the MBONα3 neurons and dopamine synthesis in the V2 neurons.…”
Section: Resultssupporting
confidence: 87%
“…We found that KCs are cholinergic (as in (Barnstedt et al, 2016; Perrat et al, 2013)), the DAL neuron is GABAergic (previously shown by (Chen et al, 2012)), both the MBON-γ5β′2a and MBON-β2β′2a neurons are glutamatergic (consistent with the findings of (Aso et al, 2014b)), and the MBONα3 and V2 neurons are cholinergic (previously shown by (Placais et al, 2013) and (Sejourne et al, 2011)). We detected evidence of potential octopamine synthesis in the MBONα3 neurons and dopamine synthesis in the V2 neurons.…”
Section: Resultssupporting
confidence: 87%
“…Data Fig. 7), consistent with findings in the adult that many KCs corelease sNPF peptide with acetylcholine 36 .…”
Section: Cc-by-ncsupporting
confidence: 90%
“…4a-d ever, we found no relationship between the similarity of the PN inputs to KC pairs and the number of KC → KC synapses formed between them (correlation coefficients 0.006 and −0.02 for left and right hemispheres; p > 0.3, comparison to shuffled network). KCs have been shown to be cholinergic in the adult 36 , so it is likely that KC → KC connections are depolarizing. Even when strong dendro-dendritic KC connections are added to our model, dimension only decreases slightly (Fig.…”
Section: Recurrent Kc Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The essentials of the organization of cholinergic neurons in these brain regions are evident in a wide range of vertebrate species from fish to primates (Giraldez-Perez et al, 2013; Hong et al, 2013; Mesulam et al, 1983; Woolf, 1991). Recent studies even find parallels to cholinergic circuits that are essential to memory encoding in invertebrates (Barnstedt et al, 2016). …”
Section: Introductionmentioning
confidence: 99%